Genomic Analysis of miR-21-3p and Expression Pattern with Target Gene in Olive Flounder - Ara Jo; Hee-Eun Lee; Heui-Soo Kim (Genomics & Informatics)
MicroRNAs (miRNAs) act as regulators of gene expression by binding to the 3’ untranslated region (UTR) of target genes. They perform important biological functions in the various species. Among many miRNAs, miR-21-3p is known to serve vital functions in development and apoptosis in olive flounder. Using genomic and bioinformatic tools, evolutionary conservation of miR-21-3p was examined in various species, and expression pattern was analyzed in olive flounder. Conserved sequences (5’-CAGUCG-3’) in numerous species were detected through the stem-loop structure of miR-21-3p. Thus, we analyzed target genes of miR-21-3p. Among them, 3’ UTR region of PPIL2 gene indicated the highest binding affinity with miR-21-3p based on the minimum free energy value. The PPIL2 gene showed high expression levels in testis tissue of the olive flounder, whereas miR-21-3p showed rather ubiquitous expression patterns except in testis tissue, indicating that miR-21-3p seems to control the PPIL2 gene expression in a complementary repression manner in various tissues of olive flounder. Taken together, this current study contributes to infer the target gene candidates for the miR-21-3p using bioinformatics tools. Furthermore, our data offers important information on the relationship between miR-21-3p and target gene for further functional study.